Alkali Metal Cation Incorporation in Conductive TiO2 Nanoflakes with Improved Photoelectrochemical H2 Generation. Issue 7 (6th April 2020) - Khorashadizade, Elham; Mohajernia, Shiva; Hejazi, Seyedsina; Mehdipour, Hamid; Naseri, Naimeh; Moradlou, Omran; Liu, Ning; Moshfegh, Alireza Z.; Schmuki, Patrik
Abstract: In this research, we investigate the effect of alkali metal cations including Li, Na and Cs in hydrothermal solution on the morphology, stability, and photoactivity of nanostructured TiO2 nanoflakes as a photoanode. The TiO2 nanoflakes are formed through hydrothermal treatment of Ti foil in 1.0 M LiOH, NaOH or CsOH at 100 °C for 3 h. By subsequent thermal reduction of the structure in an optimized Ar/H2 environment, conductive TiO2 nanoflakes were formed. The reduction treatment remarkably improves the photocurrent density of the TiO2 nanoflakes and has the highest impact on the sample treated in the NaOH alkali solution. For the nanoflakes produced in NaOH alkali solution, the bandgap is shifted to a lower value and the structure shows the most stable morphology after thermal treatment compared to nanoflakes formed in other alkali solutions. Such reduced hydrothermally treated nanoflakes formed in NaOH can generate a photocurrent density of approximately 1 mA/cm −2 vs. Ag/AgCl in 1.0 M KOH solution, which is six times higher than for pristine TiO2 . Abstract : Compare and contrast : Hydrothermal formation of TiO2 nanoflakes is studied for different alkali metal cations including Li +, Na + and Cs + in the hydrothermal solution. By subsequent thermal reduction of the structure in an optimized Ar/H2 environment, conductive TiO2 nanoflakes are formed. The morphology, stability, and photoactivity of the different nanostructured TiO2 nanoflakes are compared.